Bridging the Gap - Egeraat, Corinne van (IJSwater Films, 2008)
Verzio FF Submission 26-year-old Daniel Knoop is an accomplished, gay professional who is appointed to be a UN advisor to the Cameroonian government on exploiting natural resources. Young and determined, Daniel finds that his acclimatization to Cameroon starts off smoothly. Soon however he is faced not only with a hopelessly tangled web of corruption but also a society whose rules are alien and where homosexuality is illegal.